1987
DOI: 10.1111/j.1365-2125.1987.tb03244.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the binding of quinine and quinidine to plasma proteins.

Abstract: 1 Little is known about the comparative plasma protein binding of the antimalarial agents quinine (QN) and its isomer quinidine (QD). We have examined the in vitro binding of QN and QD to albumin, a,-acid glycoprotein, normal human plasma, and maternal and foetal umbilical cord plasma. 2 QN was more avidly bound than QD, and binding of both drugs was substantially higher to a,-acid glycoprotein than to albumin, indicating that ot,-acid glycoprotein is the more important binding protein.3 Protein and drug conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
2

Year Published

1989
1989
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 18 publications
(33 reference statements)
4
33
2
Order By: Relevance
“…This is supported by the observations in the present study; there was no relationship between serum albumin concentration and quinine binding, but a significant log linear correlation between AAG concentration and the fraction of quinine bound. However we and others (Mihaly et al, 1987) have found that plasma protein binding of quinidine (circa 70-80%) is significantly lower than quinine plasma protein binding (85-95%), and AAG affinity is correspondingly less, and so as with other isomers, findings concerning one diastereoisomer cannot necessarily be extrapolated to the other. In this study the Hill plot gave mean (s.e.…”
Section: Patientscontrasting
confidence: 53%
“…This is supported by the observations in the present study; there was no relationship between serum albumin concentration and quinine binding, but a significant log linear correlation between AAG concentration and the fraction of quinine bound. However we and others (Mihaly et al, 1987) have found that plasma protein binding of quinidine (circa 70-80%) is significantly lower than quinine plasma protein binding (85-95%), and AAG affinity is correspondingly less, and so as with other isomers, findings concerning one diastereoisomer cannot necessarily be extrapolated to the other. In this study the Hill plot gave mean (s.e.…”
Section: Patientscontrasting
confidence: 53%
“…This may be compounded further by differences in distribution and plasma protein binding which have not been assessed in this study. It is known that quinine is highly protein bound (92%) and that the percentage binding varies directly with plasma protein concentration (Mihaly et al, 1987). Patients with kwashiorkor and malaria treated with quinine should be carefully monitored to see whether there are any clinical correlates with the pharmacokinetic changes.…”
Section: Discussionmentioning
confidence: 99%
“…This has important implications since, theoretically, the shift from high-affinity to lowaffinity binding may influence the ability of compounds to cross biological membranes. Indeed, differences in orosomucoid binding have been shown to alter hepatic extraction ratio of quinidine (Mansor et al, 1991), a drug that is bound to both orosomucoid and albumin (Mihaly et al, 1987).…”
Section: Discussionmentioning
confidence: 99%